Sunflower genetic, genomic and ecological resources. (8th October 2012) - Kane, Nolan C.; Burke, John M.; Marek, Laura; Seiler, Gerald; Vear, Felicity; Baute, Gregory; Knapp, Steven J.; Vincourt, Patrick; Rieseberg, Loren H.
Abstract: Long a major focus of genetic research and breeding, sunflowers ( Helianthus ) are emerging as an increasingly important experimental system for ecological and evolutionary studies. Here, we review the various attributes of wild and domesticated sunflowers that make them valuable for ecological experimentation and describe the numerous publicly available resources that have enabled rapid advances in ecological and evolutionary genetics. Resources include seed collections available from germplasm centres at the USDA and INRA, genomic and EST sequences, mapping populations, genetic markers, genetic and physical maps and other forward‐ and reverse‐genetic tools. We also discuss some of the key evolutionary, genetic and ecological questions being addressed in sunflowers, as well as gaps in our knowledge and promising areas for future research.